1
$\begingroup$

I´ve tried at least dozen ways to convert DNF to CNF, yet I always end up with something wrong. Here is the DNF: (B ∧ D) ∨ (C ∧ D) ∨ (¬D ∧ ¬B) ∨ (¬D ∧ ¬C) .

Is there someone who can help me with it ?

$\endgroup$
1
$\begingroup$

Question already answered here Boolean algebra - Converting DNF form to CNF avoid posting duplicate questions or asking for your homework

$\endgroup$
  • $\begingroup$ Yes I know about this one, but it's not the same like mine. $\endgroup$ – AlZiSVK Oct 2 '19 at 12:20
  • 1
    $\begingroup$ @AlZiSVK No, not exactly the same ... but at the start of my Answer there, I give several examples of how to use Distribution, and from those examples you can certainly figure out how it works in your case as well. $\endgroup$ – Bram28 Oct 2 '19 at 21:15

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.